Designing an IAM Framework with Oracle Identity and Access Management Suite - Scheidel Jeff (ADBS, 2010)
Maintain a high-performance, fully integrated security foundation across your enterprise using the detailed information in this Oracle Press guide. Designing an IAM Framework with Oracle Identity and Access Management Suite explains how to reduce risk exposure by effectively managing your full spectrum of users. Learn how to create and provision accounts, employ strong authentication and authorization, integrate legacy applications, and handle regulatory compliance. The latest performance-testing, self-auditing, and business intelligence reporting techniques are also covered in this comprehensive resource.